An integrated transport strategy - making it happen! (Thomas Telford, 1998)
This is a collection of papers on integrating transport that were presented at a seminar in Abergavenny in 1998.
Keywords: Transportation -- Great Britain -- Congresses.; Transportation and state -- Great Britain -- Congresses.; elektronické knihy; electronic books